' دور الإتصال العمومي في تحسين الصورة الذهنية للمؤسسة العمومية - دراسة ميدانية بوساطة الجمهورية لولاية سوق أهراس ' - ركاب شهرزاد; بوغديري سهام (My University, 2022)
Abstract: This study, entitled "The Role of Public Communication in Improving the Public Institution's Public Image - A Field Study by the Republic's Ombudsman in the Wilaya of Souk Ahras," addresses a communication phenomenon that continues to occupy researchers, experts, and higher authorities, and attracts their attention as a central issue in public services and public institutions. In this context, this study sought to uncover the role played by public communication in improving the public image of the public service - the local delegation of the Republic's Ombudsman in the Wilaya of Souk Ahras. The study began with the following central question: - What role does public communication play in improving the public image of the public institution - the Republic's Ombudsman as a model? From this, the following sub-questions emerged: - What are the public communication methods adopted by the Republic's Ombudsman in improving this image? - What are the methods and forms of public communication practiced within the Republic's Ombudsman institution? - How do the form and means of public communication affect the image formed by citizens regarding public institutions? - What is the degree of citizen appreciation for the measures taken by the Republic's Ombudsman to improve service? - What are the obstacles that limit the effectiveness of public communication in improving the public's image among the external public? - What are the dimensions of the public image of the Republic's Ombudsman institution? - Does providing citizens with information through information and communication technology and social media contribute to improving the public image of the Republic's Ombudsman institution? This study sought to explore, from a communication perspective, the role of public communication in improving public image. The study, conducted on a sample of employees and citizens at the local delegation of the Republic's Ombudsman, shows that public communication contributes to improving the public image of the local delegation of the Republic's Ombudsman - Souk Ahras. --------------------------------- ملخص: تتناول هذه الدراسة، المعنونة "دور الاتصال العام في تحسين الصورة العامة للمؤسسة العمومية - دراسة ميدانية لأمين مظالم الجمهورية بولاية سوق أهراس"، ظاهرة اتصالية لا تزال تشغل الباحثين والخبراء والسلطات العليا، وتحظى باهتمامهم كقضية محورية في الخدمات العامة والمؤسسات العمومية. وفي هذا السياق، سعت هذه الدراسة إلى الكشف عن دور الاتصال العام في تحسين الصورة العامة للمؤسسة العمومية - المندوبية المحلية لأمين مظالم الجمهورية بولاية سوق أهراس. انطلقت الدراسة من السؤال المحوري التالي: - ما دور الاتصال العام في تحسين الصورة العامة للمؤسسة العمومية - أمين مظالم الجمهورية نموذجًا؟ - ومن هنا انبثقت الأسئلة الفرعية التالية: - ما هي أساليب الاتصال العام التي يتبعها أمين مظالم الجمهورية في تحسين هذه الصورة؟ - ما هي أساليب وأشكال الاتصال العام المتبعة داخل مؤسسة أمين مظالم الجمهورية؟ - - كيف يؤثر شكل ووسائل الاتصال العام على الصورة التي يكوّنها المواطنون عن المؤسسات العامة؟ - ما مدى تقدير المواطنين للإجراءات التي يتخذها أمين مظالم الجمهورية لتحسين الخدمة؟ - ما هي المعوقات التي تحد من فعالية الاتصال العام في تحسين صورة الجمهور لدى الجمهور الخارجي؟ - ما هي أبعاد الصورة العامة لمؤسسة أمين مظالم الجمهورية؟ - هل يُسهم تزويد المواطنين بالمعلومات عبر تكنولوجيا المعلومات والاتصالات ووسائل التواصل الاجتماعي في تحسين الصورة العامة لمؤسسة أمين مظالم الجمهورية؟ سعت هذه الدراسة إلى استكشاف دور الاتصال العام في تحسين الصورة العامة من منظور اتصالي. وقد أظهرت الدراسة، التي أجريت على عينة من الموظفين والمواطنين بالمندوبية المحلية لأمين مظالم الجمهورية، أن الاتصال العام يُسهم في تحسين الصورة العامة للمندوبية المحلية لأمين مظالم الجمهورية - سوق أهراس.
Keywords: الإتصال العمومي، الصورة الذهنية، المؤسسة العمومية